2008
DOI: 10.1088/0957-4484/19/14/145701
|View full text |Cite
|
Sign up to set email alerts
|

Experimental study on the surface modification of Y2O3:Tm3+/Yb3+nanoparticles to enhance upconversion fluorescence and weaken aggregation

Abstract: In order to improve the solubility of doped nanoparticles in solutions, Y(2)O(3):Tm(3+)/Yb(3+) nanoparticles were synthesized using the Pechini-type sol-gel method, and their surfaces were modified with amino or carboxylic functional groups using ligand-capped and ligand-exchanging methods. The nanoparticles with modified surfaces were characterized by transmission electron microscopy (TEM), Fourier transform infrared (FT-IR) spectroscopy and zeta potential (ζ), and their photoluminescence was studied by fluor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
28
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 70 publications
(30 citation statements)
references
References 30 publications
2
28
0
Order By: Relevance
“…The upconversion enhancement mechanism is approximatively similar to those of the core-shell type upconversion nanoparticles from our previous works [52][53][54] and is simply explained in supplemental data III.…”
Section: Surface Oxidation Of Hydrophobic Ligands Andsupporting
confidence: 59%
“…The upconversion enhancement mechanism is approximatively similar to those of the core-shell type upconversion nanoparticles from our previous works [52][53][54] and is simply explained in supplemental data III.…”
Section: Surface Oxidation Of Hydrophobic Ligands Andsupporting
confidence: 59%
“…There exists a need to develop a simple but effective method that will allow the secondary nucleation of silica particles to be avoided when applying silica coatings Because thick shells will prevent upconversion nanocrystals from behaving as bioprobes [22], only the effect of thin shells on the luminescence properties of Y-Y-H has been investigated. As shown in Figure 3 Recently, Lü et al [20,21] reported that in addition to the decrease of surface defects, a coating could also change the crystal field around the dopant ions at the surface of the nanoparticles. However, it is thought that the silica/aminosilane coating used herein has little influence on the crystal field around the dopant ions at the surface because the position and shape of the emission bands do not change upon addition of the coating (see Figure 3) [32,33].…”
Section: Y-y-h/s1 Y-y-h/s2 Y-y-h/s3 and Y-y-h/s-n1 Samplesmentioning
confidence: 99%
“…Yttria-based upconversion nanocrystals (YUNs) are well known as an excellent candidates for upconversion fluorescent bioprobes because of their favorable chemical and thermal stability, nontoxicity and high emissive intensity [12][13][14][15][16][17][18][19][20][21]. However, unmodified YUNs tend to agglomerate in water and lack surface groups capable of coupling biomolecules, which limits their application in bioassays.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, it has been reported that the efficiency of the Ln emission processes and photostability may be also improved by the silica layer, which minimises the quenching of the excited states in the Ln cations located on the nanoparticles surface through interaction with surface OH groups [7] and [8]. Usually, these lanthanide nanophosphors-silica composites are prepared by different liquid phase procedures [4], [5] and [6], which involve an initial synthesis and purification of the luminescent nanoparticles and in a second stage, the surface precipitation of the silica layers.…”
Section: Introductionmentioning
confidence: 99%